Social-demographic factors and nursing diagnosis in patients with kidney transplant - Ana Luisa Brandão de Carvalho Lira; Marcos Venícios de Oliveira Lopes; Lúcia de Fátima da Silva; Thelma Leite de Araujo (Rev Rene)
Analyze the statistical associations among nursing diagnoses identifi ed in patients with renal transplant and their socioeconomic factors. A cross-sectional study performed in a university hospital in Fortaleza, from December 2004 to April 2005. 38 nursing diagnosis were identifi ed. Ten diagnosis presented frequency above the 75th percentile: risk of Infection; disturbed sensory perception; visual; hearing; Sleep pattern disturbance; Imbalanced nutrition; fatigue; sexual dysfunction; disturbed sensory perception: acute pain, more than body requirements; The nursing diagnosis study contributes to increasing the knowledge of realty of these patients, which is a necessary step for the establishment of nursing assistance to the renal transplanted, as well as for the direction of outcomes to be reached aiming the improvement of life quality.